The role of atmosphere and ocean physical processes in ENSO in a perturbed physics coupled climate model - S. Y. Philip; M. Collins; G. J. van Oldenborgh; B. J. J. M. van den Hurk (Ocean Science, 2010)
We examine the behaviour of the El Niño – Southern Oscillation (ENSO) in an ensemble of global climate model simulations with perturbations to parameters in the atmosphere and ocean components respectively. The influence of the uncertainty in these parametrisations on ENSO are investigated systematically. The ensemble exhibits a range of different ENSO behaviour in terms of the amplitude and spatial structure of the sea surface temperature (SST) variability. The nature of the individual feedbacks that operate within the ENSO system are diagnosed using an Intermediate Complexity Model (ICM), which has been used previously to examine the diverse ENSO behaviour of the CMIP3 multi-model ensemble. Unlike in that case, the ENSO in these perturbed physics experiments is not principally controlled by variations in the mean climate state. Rather the parameter perturbations influence the ENSO characteristics by modifying the coupling feedbacks within the cycle. The associated feedbacks that contribute most to the ensemble variations are the response of SST to local wind variability and damping, followed by the response of SST to thermocline anomalies and the response of the zonal wind stress to those SST anomalies. Atmospheric noise amplitudes and oceanic processes play a relatively minor role.